Regulation of oil well cement paste properties by nanoclay: Rheology, suspension stability and hydration process. (9th May 2023) - Li, Pengpeng; Hu, Miaomiao; Liu, Ming; Zhang, Hang; Zhao, Jiaqi; Xia, Xiujian; Guo, Jintang
Highlights: The nanoclay strengthened the grid structure assembled by charged copolymer and nanoclay and cement colloidal particles. The addition of nanoclay can significantly the suspension stability of cement paste under high temperature. The nanoclay colloidal particle promoted cement hydration and improved mechanical properties of hardened cement stone. The nanoclay colloidal particle can serve as the nucleation sites for generation of CSH. Abstract: Enhanced grid reconstruction ability of oil well cement paste has been confirmed as a promising solution to inhibit particle sedimentation caused by the uncontrolled rheological property at high temperatures. The effect of nanoclay dispersions of Bentonite and Laponite on the rheological property, suspension stability and hydration process of the cement pastes was examined. The nanoclay dispersions (especially Laponite) enhanced the dynamic reversible gel structure and improved its reconstruction ability. The addition of nanoclay effectively inhibited the sedimentation of solid particles at high temperatures due to form a gel structure by polymer admixtures, nanoclay and cement colloidal particles. Moreover, the nanoclay facilitated the cement hydration and enhanced the mechanical property for the nucleation and filler effect. Accordingly, the nanoclay can enhance thixotropy and suspension stability of the early cement paste and increase the mechanical strength of hardened cement stones, which contributes to improving the sealing integrity of cement sheath.